The patients' experiences of burden of neurofibromatosis: A qualitative study - Samira Foji (Iranian Journal of Nursing and Midwifery Research, 2021)
Background: Neurofibromatosis Type 1 (NF1) is a common autosomal disorder; the criteria for the diagnosis of NF1 includes café au lait spots, freckling, and Neurofibromas (NF). Skin symptoms have a major impact on patients' Quality of Life (QOL) but little is known about the burden of the disease on patients. The aim of this study was to explore the experiences of patients with NF. Materials and Methods: Using purposive sampling, 20 participants were enrolled in this qualitative content analysis study. The study was carried out between 2019 and 2020. Unstructured interviews and field notes were used to gather data. Data collection was stopped when data saturation was achieved. Results: Data analysis revealed 14 subcategories and 4 categories including “failing and falling behind in life”, “deprivation and restriction”, “social isolation”, and “ineffective adaptation to the disease”, which indicate the perception of patients with NF. Conclusions: In addition to the physical burden due to physical complications and problems, NF imposes a high degree of psychological and social burden on patients causing mental conflicts, which in turn results in them failing and falling behind in life. These findings illustrate the need to develop strategies and use multidisciplinary approaches to support patients, and thus to reduce the burden of NF.